Minimizing growth of Gypsophyla rupestris Kupr. callus tissues (Experimental biology, 2015)
The callus tissues of Gypsophyla rupestris Kupr. were obtained for the first time from ascetic sprouts in Murashige and Skoog (МS) medium with phytohormones BAP- 1 mg/l : IAA- 2 mg/l.For minimizing growth of Gypsophyla rupestris Kupr. callus tissues was used 50 % and 100 % MS medium with retardants, together with low positive temperatures (+5оС). Optimum concentration of retardants for delay of growthregulating activity and viability renewal, after transfer to normal conditions of callus tissues are 5%, 10 % sucrose and combination of 5 % sucrose and 2 % mannite.
Keywords: Gypsophyla rupestris Kupr.; callus culture; minimizing; deposition; retardants; collection of in vitro